System Structure, Unjust War, and State Excusability. Issue 1 (8th February 2023) - Rubin, David
Abstract: This article seeks to bridge the interdisciplinary gap between just war theory (JWT) and international relations (IR) by introducing into the former discipline key theoretical and empirical insights from the latter discipline. Specifically, the article argues that traditional JWT is deficient as a normative account of war because it constitutes what Kenneth Waltz calls a "unit-level" theory, operating at the level of the individual state and evaluating the morality of a given war solely by reference to a list of state-level factors (e.g., just cause, proportionality, etc.). In this manner, JWT fails to take account of the systemic, or structural, correlates of international armed conflict. In particular, it fails to incorporate insights from the leading mainstream IR theories of neorealism, institutionalism, and constructivism in regard to how the international distribution of material capabilities, institutions, and ideas codetermines the nature and likelihood of war. To remedy these inadequacies of JWT, a "multilevel" approach to the morality of war is put forward according to which unit-level factors are required to be weighted by systemic factors. Pursuant to this approach, if a state has initiated or participated in a war that is assessed as unjust through the unit-level lens of traditional JWT, the state itself can still sometimes be partially excused for that war once systemic factors have been considered.